2015
DOI: 10.1111/jace.14033
|View full text |Cite
|
Sign up to set email alerts
|

Novel Three‐Dimensional Extrusion of Multilayered Ceramic/Camphene Mixture for Gradient Porous Ceramics

Abstract: This study proposes an innovative way of creating porous ceramics with a unique gradient porous structure using threedimensional extrusion of a multilayered ceramic/camphene feed rod, denoted as "3D-Ex m ". This 3D-Ex m technique utilizes the wall slip phenomenon during the extrusion process, which can create a gradient core/shell structure with a gradual change in the core/shell thickness ratio. In addition, the microstructure of ceramic filaments can be tuned through the use of the camphene as a pore-forming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Different sublimable vehicles have also been explored and optimized for processing of porous materials, like camphene mixtures, as originally reported by Halloran et al. , and most recently reported by Choi et al . to produce 3D‐extrusion multilayered ceramics.…”
Section: Macroporous Ceramic Structures Enabled By Colloidal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Different sublimable vehicles have also been explored and optimized for processing of porous materials, like camphene mixtures, as originally reported by Halloran et al. , and most recently reported by Choi et al . to produce 3D‐extrusion multilayered ceramics.…”
Section: Macroporous Ceramic Structures Enabled By Colloidal Processingmentioning
confidence: 99%
“…The green sample is then sintered to strengthen the component. Different sublimable vehicles have also been explored and optimized for processing of porous materials, like camphene mixtures, as originally reported by Halloran et al, 251,252 and most recently reported by Choi et al 253 to produce 3D-extrusion multilayered ceramics. Ice templating can produce porosities between 20 and 80%, with pore sizes ranging between 5 to 100 lm.…”
Section: Ice Templatingmentioning
confidence: 99%
“…The availability of 3D reticular architecture can effectively increase the contact area between PM and ceramic foams and enables high filtration efficiency . This advantage also facilitates gas flow and has been instrumental in the recent emergence of solid‐liquid, gas‐liquid separation . Among numerous approaches to fabricate ceramic foams with such architecture features, polyurethane (PU) foaming is widely adopted due to its advantages of possessing 3D reticular architecture, short preparation period, and adjustable porosity .…”
Section: Introductionmentioning
confidence: 99%
“…9 This advantage also facilitates gas flow and has been instrumental in the recent emergence of solid-liquid, gas-liquid separation. [10][11][12] Among numerous approaches to fabricate ceramic foams with such architecture features, polyurethane (PU) foaming is widely adopted due to its advantages of possessing 3D reticular architecture, short preparation | 5577 LIU et aL. period, and adjustable porosity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ceramic core-shell rods based on zirconia and/or other ceramic materials have been applied as PZT actuators [3], bioceramic implants with a bone structure [7][8][9], solid oxide fuel cells [10,11] or as oxygen separation membranes [12,13]. Such structures can be fabricated by many methods such as freeze casting [5,7,14,15], slip casting or extrusion followed by a coating process [6,16,17], electrophoretic deposition [18], and co-extrusion [3,4,19,20]. The last mentioned method, co-extrusion, exhibits many processing advantages such as simple production with excellent interface between the core and shell materials, lowcost production and better mechanical properties of coextruded bodies compared with other shaping methods [16,21,22].…”
Section: Introductionmentioning
confidence: 99%